Designing Water Level Control Equipment Using SMS-Based Ultrasonic Sensors - Harrischandra, I Putu Eddy Aditya; Satriya Wibawa, I Made; Wendri, Nyoman (BULETIN FISIKA; Vol 23 No 2 (2022): BULETIN FISIKA August EditionDO - 10.24843/BF.2022.v23.i02.p07, 2021)
The controlled water level using an ultrasonic sensor and Short Message Service (SMS) based has been successfully developed. The developed tools using an Arduino UNO ATmega328 as microcontroller, an ultrasonic sensor for measuring the water level, SMS module SIM 800L to receiver and message sender from developed tools to handphone, LCD 16 x 2 as a display, and Relay module as automatic switch that would activate and deactivate the water pump. Before testing the developed tools, the ultrasonic sensor need to be calibrated. Calibration is carried out for adjusting the sensor’s output with the measuring instrument which is a ruler with 1 mm precision. The result of the developed tools has precision value 99.99% and then showing the developed tools worked well.